Odpowiedź :
1/2 -(1,2 * 5/12 - a) : 1/8 = 1,3
1/2 - (1/2 - a)/1/8 = 1,3
1/2 - (4 - 8a) = 1,3
1/2 - 4 + 8a = 1,3
-3,5 + 8a = 1,3
8a = 1,3+3,5
8a = 4,8 |:8
a = 0,6
Spr.: L= 1/2 - (1,2*5/12 -0,6):1/8 = 1/2 - (0,5-0,6)/1/8= 1/2 - (-0,1)/1/8 = 1/2 +0,8 = 1,3
P=1,3
L=P
1/2 - (1/2 - a)/1/8 = 1,3
1/2 - (4 - 8a) = 1,3
1/2 - 4 + 8a = 1,3
-3,5 + 8a = 1,3
8a = 1,3+3,5
8a = 4,8 |:8
a = 0,6
Spr.: L= 1/2 - (1,2*5/12 -0,6):1/8 = 1/2 - (0,5-0,6)/1/8= 1/2 - (-0,1)/1/8 = 1/2 +0,8 = 1,3
P=1,3
L=P
½-(1,2×5/12-a):⅛=1,3
½-1,2×5/12+a:⅛=1,3
½-12/10×5/12+a:⅛=1,3
½-½+a×8/1=1,3
8a=1,3/:8
a=0,1625
½-1,2×5/12+a:⅛=1,3
½-12/10×5/12+a:⅛=1,3
½-½+a×8/1=1,3
8a=1,3/:8
a=0,1625
1/2 -(1,2 * 5/12 - a) : 1/8 = 1,3
½-(½-a):⅛=13/10
-(½-a)*8=13/10 - 5/10
-4+8a=8/10
8a=8/10+40/10
8a=48/10
a=48/10*1/8=6/10=3/5
½-(½-a):⅛=13/10
-(½-a)*8=13/10 - 5/10
-4+8a=8/10
8a=8/10+40/10
8a=48/10
a=48/10*1/8=6/10=3/5